2014
DOI: 10.1155/2014/852954
|View full text |Cite
|
Sign up to set email alerts
|

Review of Hyperuricemia as New Marker for Metabolic Syndrome

Abstract: Hyperuricemia has long been established as the major etiologic factor in gout. In recent years, a large body of evidence has accumulated that suggests that hyperuricemia may play a role in the development and pathogenesis of a number of metabolic, hemodynamic, and systemic pathologic diseases, including metabolic syndrome, hypertension, stroke, and atherosclerosis. A number of epidemiologic studies have linked hyperuricemia with each of these disorders. In some studies, therapies that lower uric acid may preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
129
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 67 publications
(72 reference statements)
4
129
0
11
Order By: Relevance
“…6 There are epidemiological studies showing a relationship between SUA levels and the markers of systemic inflammation. 20,21 In several population-based studies, in healthy men and women, and also in patients with metabolic syndrome and patients with chronic heart failure, SUA has been shown to be positively correlated with CRP, IL-6 and TNFalpha.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 There are epidemiological studies showing a relationship between SUA levels and the markers of systemic inflammation. 20,21 In several population-based studies, in healthy men and women, and also in patients with metabolic syndrome and patients with chronic heart failure, SUA has been shown to be positively correlated with CRP, IL-6 and TNFalpha.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In several population-based studies, in healthy men and women, and also in patients with metabolic syndrome and patients with chronic heart failure, SUA has been shown to be positively correlated with CRP, IL-6 and TNFalpha. 6,[20][21][22][23][24] Recently, an association between hyperuricaemia and HT, atherosclerosis, cardiovascular diseases and chronic kidney diseases has been observed in several studies. 20 Epidemiological studies have demonstrated a close relationship between SUA levels and the prevalence of metabolic syndrome or its components, independent of classical risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In addition to cardiovascular risk, the metabolic syndrome is strongly associated with a large number of clinical conditions like non-alcoholic fatty liver disease, cholesterol gall stones, obstructive sleep apnoea, hyperuricemia, polycystic ovarian syndrome and psoriasis. [3][4][5][6][7][8] The exact relationship between most of these conditions and metabolic syndrome is an area of ongoing research. Currently different diagnostic criteria exist for the diagnosis of Department of Medicine, Uttar Pradesh University of Medical Sciences, Saifai, Etawah, Uttar Pradesh, India metabolic syndrome including those proposed by NCEP:ATP III (National Cholesterol Education Program: Adult Treatment Plan III), IDF (International Diabetes Federation) and WHO (World Health Organization).…”
Section: Introductionmentioning
confidence: 99%
“…El ácido úrico (AU) es el producto final del metabolismo de las purinas 1 . Los valores de AU pueden incrementarse en respuesta tanto a factores ambientales como genéticos, conduciendo a hiperuricemia, que se define clínicamente como concentraciones sé-ricas de AU mayores de 7 mg/dl en hombres o 6 mg/ dl en mujeres 2 .…”
Section: Introductionunclassified